UNCHARTED WATER : - Zuliarti Wa Ode; Fitriah Faisal (International Journal of Law in Changing World)
Digital technology has complicated copyright protection, particularly in Indonesia, where weak laws, poor enforcement, and low awareness fuel piracy. Modernizing regulations, improving enforcement, and promoting education about intellectual property rights are essential to fostering innovation, safeguarding creators, and supporting the creative economy in the digital era. This study evaluates Indonesia's copyright framework in the digital era, focusing on its legal adaptability, enforcement effectiveness, public awareness, economic impacts, and potential insights from global best practices to enhance the creative economy and tackle digital piracy challenges. This study employs comparative hermeneutics, including legal analysis of Indonesia's copyright laws, international benchmarks, and case studies of successful anti-piracy efforts to study enforcement mechanisms and economic impacts to offer actionable insights for effectively adapting Indonesia's copyright framework. The authors conclude that Indonesia must strengthen its legal framework; only by aligning with global standards like TRIPS can Indonesia safeguard creators’ rights, enhance enforcement, and ensure competitiveness in the digital economy.